The Use of development news case studies of India, Malaysia, Ghana, and Thailand - Lent, John A.; Vilanilam, John V.; De Fontgalland, Guy.; Asian Mass Communication Research and Information Centre (Singapore Asian Mass Communication Research and Information Centre (AMIC), 1979)
The genesis of this monograph was in 1972-74 when John Lent was in Malaysia teaching at the Universiti Sains Malaysia. It seemed that at least weekly, a government official made a public statement about the role mass media should assume in a developing nation such as Malaysia. Usually the statements included the word "development" or some aspect of it. To gauge the intensity of this campaign to use media for development purposes, students in Lent's classes were assigned to do a series of content analysis of print, broadcast and folk media. The findings of those projects confirmed at least in part that there was a concerted effort to change the format and contents of the mass media.

Simultaneously, officials of other Third World nations and communications specialists made similar statements about mass media used in support of national development. However, the research literature showed virtually no studies on the amount and type of development news used by the media. Nowhere was it possible to find answers to questions such as: Are mass media in Third World countries heeding the advice of the officials and others in regard to usage of development news? Can development news be separated from governmental or political news in these cultures?

In 1974, we conceived a project which aimed to systematically analyse the usage of governmental, political and development news in four Indian dailies. The Vilanilam thesis which resulted defined a list of categories for the three types of news which was then used in part or in whole in three other master's theses which Lent supervised, two with Vilanilam's help. The objective was to seek comparative data on the use of development news in various media of different Third World nations. The result is this monograph with information on development news usage in newspapers, broadcasts and news agency copy of India, Malaysia, Ghana and Thailand.

Hamima Dona Mustafa, Lecturere at Universiti Sains Malaysia, was a master's degree candidate at Ohio University when she decided to replicate with the help of the editors of this monograph the Vilanilam study, using two Malay and one English Language newspapers of Malaysia as her case studies.

Emmanuel Osae-Asare, formerly with Ghana Broadcasting and now a Ph. D. student at New York University, analysed the development news contents of two national dailies and the national news service of Ghana. Oranuj Yunjanondh, Lecturer at Thammasat University in Bangkok, concentrated on the use of governmental and development news in three Thai broadcasting stations--one each in the governmental, educational and quasi-private categories.

The organisation of this monograph includes a general discussion of development and some development theory, a brief chapter on the evolution of the concept of development communication, followed by the four case studies in the order in which they were completed.

From our search of literature, we believe this monograph represents the first comparative content study of the use of development information by print and broadcast media in Asian and African countries.

-John A. Lent and John V. Vilanilam,
18 October 1979
Philadelphia
Includes bibliographical references.
Donated.
Keywords: Mass media -- Developing countries -- Case studies